How do we know what information sharing is really worth? : exploring methodologies to measure the value of information sharing and fusion efforts - Jackson, Brian A. (Brian Anthony); Homeland Security and Defense Center; Rand Justice, Infrastructure, and Environment (Organization); Rand Corporation. National Security Research Division; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2014)
Since the terrorist attacks of September 11, 2001, the sharing of intelligence and law enforcement information has been a central part of U.S. domestic security efforts. Though much of the public debate about such sharing focuses on addressing the threat of terrorism, organizations at all levels of government routinely share varied types of information through multiagency information systems, collaborative groups, and other links. Given resource constraints, there are concerns about the effectiveness of information-sharing and fusion activities and, therefore, their value relative to the public funds invested in them. Solid methods for evaluating these efforts are lacking, however, limiting the ability to make informed policy decisions. Drawing on a substantial literature review and synthesis, this report lays out the challenges of evaluating information-sharing efforts that frequently seek to achieve multiple goals simultaneously; reviews past evaluations of information-sharing programs; and lays out a path to improving the evaluation of such efforts going forward.
Caption title.
"RAND Corporation."
"This research was conducted within the RAND Homeland Security and Defense Center ... a joint center of two research divisions: RAND Justice, Infrastructure, and Environment, and the RAND National Security Research Division"--Back cover.
Includes bibliographical references (p. 27-30).
Also available on the internet via WWW in PDF format.
Description based on print version record.